ANALISIS TINGKAT KEPUASAN WALI MURID TERHADAP SISTEM ZONASI SEKOLAH - Devi Mariatul Qiptiah; Sophian Djaka Prawira (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study is to analyze the level of satisfaction of guardians of students who live far away (more than 3 kilometers) and guardians of students who live near (less than 3 kilometers) of SMPN 1 Jember with respect to the New Student Registration (PPDB) zoning system.The research method used is qualitative. The research implementation stage is a preliminary study, determining research methods, collecting data, analyzing data, validating data, and compiling reports. Research informants were determined purposively. Data collection techniques using observation, interviews, and documentation. Data analysis techniques through data reduction, data exposure, and drawing conclusions.The results of the study found that first, an analysis of the level of satisfaction of the guardians of students who live far from SMPN 1 Jember to the PPDB zoning system that is not satisfied. The guardians of students hope that the implementation of new student admissions through the zoning system may continue to be enforced on the condition that they continue to provide equal opportunities to students who will enter through the zoning route. Second, the analysis of the level of satisfaction of parents who live near from SMPN 1 Jember to the PPDB zoning system is not satisfied because even though their children can easily enter through the zoning system, it is still hoped that there will be a balance between the zoning path and achievement.